Reverberations: violence across time and space - Navaro-Yashin, Yael; Biner, Zerrin Özlem; Bieberstein, Alice von; Altuğ, Seda (The ethnography of political violence, 2021)
The turn to the nonhuman in the humanities and social sciences has arguably been mobilized through a washing away of political violence, its histories, and its traces. Reverberations aims to redress this problem by methodologically and conceptually placing political violence and nonhuman entities side by side. The volume generates a new framework for the study of political violence and its protracted aftermath by attending, through innovative ethnographic and historical studies, to its distribution, extension, and endurance across time, space, materialities, and otherworldly dimensions, as well as its embodiment in subjectivities, discourses, and imaginations. Collectively, in the study of political violence, the contributions focus on human agencies and experiences in engagement with nonhuman entities such as objects, land, fields, houses, buildings, treasures, trees, spirits, saints, and prophets. In a variety of contexts, the scholars herein ask the crucial question: What can be learned about political violence by analyzing it in the terrain of relationality between human beings and nonhuman entities? How are things such as objects, spaces, natural phenomena, or spiritual beings entwined in histories of political violence? And vice versa—how are histories of political violence implicated in nonhuman things? Yael Navaro is Professor of Social Anthropology at the University of Cambridge, UK. Zerrin Özlem Biner is Lecturer in Social Anthropology at the University of Kent, Canterbury, UK. Alice von Bieberstein is Assistant Professor at Humboldt-Universität zu Berlin, Germany.